PENINGKATAN MUTU KBM MATA KULIAH TRANSLATION 1 MELALUI METODE PEMBELAJARAN GROUP-TO-GROUP EXCHANGE - Lilik Untari (University of Muhammadiyah Purwokerto, 2009)
Teaching-learning result of Translation 1 of second semester students is not satisfying. It can be seen from the studentsâ average score that is under 2,5; the percentage of studentsâ attendance is 93%, while the lecturerâs presence has been 100%. Therefore, new model of teaching-learning activity for this subject is needed to increase the quality of the teaching-learning activity. The new model applied for this study is group-to-group exchange. The object of the research is the students who take Translation 1 class in 2008. The object is divided into 2 groups. Group 1 is given treatment by applying group-to-group exchange model and group 2 as the control is treated by delivering speech model. The Indicators are lecturer's activity, students' activity, and students' academic achievement. The result of the research shows that (1) lecturer's activity is increased by producing more papers with new references (50% in the mid of the research and 75% at the end of the research); (2) at the end of the research students' activity is increased by asking more questions ( 10 x if it is compared with the control), answering questions (6x compared with control), and presentation (4x compared with the control); (3) the creativity is increased by producing papers (10 x compared with the control); and (4) the class average score is increased (2,9 compared with 2,4) and students's percentage with the score of > 2,5(41 compared with 39).